2000
DOI: 10.1016/s0735-1097(00)00767-1
|View full text |Cite
|
Sign up to set email alerts
|

Nonsurgical septal reduction therapy for hypertrophic obstructive cardiomyopathy: one-year follow-up

Abstract: Nonsurgical septal reduction therapy is an effective therapy for symptomatic patients with hypertrophic obstructive cardiomyopathy with persistence of the favorable outcome up to one year after the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
87
0
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(95 citation statements)
references
References 19 publications
5
87
0
3
Order By: Relevance
“…9,22 Previous echocardiographic studies have shown ambiguous results with respect to reduction of LV posterior wall thickness. [7][8][9][10][11][23][24][25][26] Tomographic techniques such as electron-beam computed tomography and CMR may be more accurate and reproducible than echocardiographic measurements and LV mass calculations. Electron-beam computed tomography showed septal mass reduction 1 week after ASA and found reduced remote mass at 4 to 6 months of follow-up.…”
Section: Changes In Septal and Remote Myocardial Mass After Asamentioning
confidence: 99%
“…9,22 Previous echocardiographic studies have shown ambiguous results with respect to reduction of LV posterior wall thickness. [7][8][9][10][11][23][24][25][26] Tomographic techniques such as electron-beam computed tomography and CMR may be more accurate and reproducible than echocardiographic measurements and LV mass calculations. Electron-beam computed tomography showed septal mass reduction 1 week after ASA and found reduced remote mass at 4 to 6 months of follow-up.…”
Section: Changes In Septal and Remote Myocardial Mass After Asamentioning
confidence: 99%
“…In patients suffering from hypertrophic cardiomyopathy exhibiting a LV outflow tract gradient at rest of less than 40 mmHg, who present with advanced symptoms of angina and/or dyspnea [39], SED was performed before and after an application of ethanol. Only patients with induced gradients of more than 60 mmHg were considered candidates for the procedure.…”
Section: New Uses For Echocardiographic Stress Testsmentioning
confidence: 99%
“…Left ventricular outflow tract (LVOT) obstruction is an important complication of hypertrophic cardiomyopathy, related to symptoms, functional limitations, and prognoses of the patients [1][2][3], and various types of medical and surgical interventions are performed to reduce the pressure gradient in LVOT [4][5][6][7][8][9][10][11][12][13][14][15]. The degree of dynamic obstruction seen in patients with hypertrophic obstructive cardiomyopathy (HOCM) can vary markedly by the physiological changes in preload, contractility, and afterload [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Transthoracic continuous-wave (CW) Doppler technique has been reported to be feasible to measure the peak velocity in LVOT and to calculate the pressure gradient through the simplified Bernoulli equation [19][20][21]. This method is completely noninvasive and in recent years has become a standard method to quantify the degree of LVOT obstruction and monitor the efficacy of the treatment [8][9][10][11][12][13][14]17].…”
Section: Introductionmentioning
confidence: 99%